Answer:
6) x = 3, y = -1 or (3, -1)
8) x = -1, y = ½ or (-1, ½)
Explanation:
Note:
I will only demonstrate problems 6 and 8 since the process of solving for the solution is practically similar for problems 6 and 7.
Given the following systems of linear equations with two variables:
Question 6
![\displaystyle\mathsf{\left \{{{Equation\:1:\:x\:+\:y=2} \atop {Equation\:2:\:2x\:-\:y=7}} \right. }](https://img.qammunity.org/2022/formulas/mathematics/high-school/5i9jqjg1xyyqslh6eudnhnmlfb8ve7pppw.png)
First, isolate y from Equation 1:
x + y = 2
x - x + y = -x + 2
y = -x + 2
Substitute the value of y in the previous step into Equation 2:
2x - (-x + 2) = 7
2x + x - 2 = 7
3x - 2 = 7
Add 2 to both sides:
3x - 2 + 2 = 7 + 2
3x = 9
Divide both sides by 3 to solve for x:
![\displaystyle\mathsf{(3x)/(3)\:=\:(9)/(3)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/2zxiym7qxo6iv8y1u6n3glb0wbytfecylg.png)
x = 3
Substitute the value of x into Equation 1 to solve for y:
x + y = 2
3 + y = 2
3 - 3 + y = 2 - 3
y = -1
Therefore, the solution to the given system is: x = 3, y = -1 or (3, -1).
Question 8:
![\displaystyle\mathsf{\left\{Equation\:1:\:3(6x\:-\:4y)\:=24} \atop{Equation\:2:\:3x\:-\:2y\:=4}} \right.}](https://img.qammunity.org/2022/formulas/mathematics/high-school/xv5eevie2pisjw8f2yiykglh5epyxed88v.png)
For Equation 2, divide both sides by -3:
![\displaystyle\mathsf{(-3(6x-4y))/(-3)=(24)/(-3) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/demp3dlgp2oa5z1hhsh1jrru1a2jlgi3a0.png)
6x - 4y = -8
Add 6x to both sides:
6x + 6x - 4y = 6x - 8
- 4y = 6x - 8
Divide both sides by -4 to isolate y:
![\displaystyle\mathsf{(-4y)/(-4)=(6x\:-\:8)/(-4) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/1i4gztn0ier8d4ismyzzsuqhz6107axb1n.png)
![\displaystyle\mathsf{y=-(3)/(2)+2}](https://img.qammunity.org/2022/formulas/mathematics/high-school/7v0mcsy3weeizdqeba1v1rpgwnwnjh6g2a.png)
Substitute the value of y from the previous step into Equation 2:
3x - 2y = -4
![\displaystyle\mathsf{3x\:-\:2\Big(-(3)/(2)+2\Big)\:=-4}](https://img.qammunity.org/2022/formulas/mathematics/high-school/hgl8kjxptoljrgyb77uixb7fxgtc0capop.png)
3x + 3 - 4 = -4
3x - 1 = -4
3x - 1 + 1 = -4 + 1
3x = -3
Divide both sides by 3 to solve for x:
![\displaystyle\mathsf{(3x)/(3)=(-3)/(3)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/47mnr7rteyuag12o4713cdvdo6cntirhdi.png)
x = -1
Substitute the value of x into Equation 2 to solve for y:
3x - 2y = -4
3(-1) - 2y = -4
-3 - 2y = -4
Add 3 to both sides:
-3 + 3 - 2y = -4 + 3
-2y = -1
Divide both sides by -2 to isolate y:
![\displaystyle\mathsf{(-2y)/(-2)=(-1)/(-2)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/5qxtwhtvdzdp98ch2hf6u9hqltgknno8tm.png)
y = ½
Therefore, the solution to the given system is: x = -1, y = ½ or (-1, ½).